2011
DOI: 10.1111/j.1528-1167.2010.02892.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral tuber count and its impact on mental outcome of patients with tuberous sclerosis complex

Abstract: Summary Purpose:  The aim of the study was to reveal the relationships between the tuber count of the brain found in patients with tuberous sclerosis complex (TSC) and their cognitive outcome. Methods:  A single‐center, retrospective analysis was performed of patients with documented TSC seen from 1988 to 2010 at the Children’s Memorial Health Institute, Warsaw, Poland. Key Findings:  Sixty‐two patients were analyzed, and there was a significant correlation between younger age at the first seizure and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 17 publications
1
45
0
2
Order By: Relevance
“…Twenty-three of these cases subsequently had genetic testing which identified a mutation, including 10 cases who did not have a confirmed clinical diagnosis when they had their first seizure, demonstrating the contribution genetic testing can make in this situation. Given evidence that seizures, particularly in young children, may contribute to cognitive impairment,18 2631 this raises important issues about monitoring for seizures and the indications for starting anticonvulsant therapy. Prospective EEG monitoring in young infants with TS has shown that the EEG often becomes abnormal with multifocal epileptic activity prior to the onset of clinically apparent seizures and there is evidence suggesting that these changes can be reversed by treatment with vigabatrin,32 33 giving better control of epilepsy and improving the cognitive and behavioural outcome 34.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three of these cases subsequently had genetic testing which identified a mutation, including 10 cases who did not have a confirmed clinical diagnosis when they had their first seizure, demonstrating the contribution genetic testing can make in this situation. Given evidence that seizures, particularly in young children, may contribute to cognitive impairment,18 2631 this raises important issues about monitoring for seizures and the indications for starting anticonvulsant therapy. Prospective EEG monitoring in young infants with TS has shown that the EEG often becomes abnormal with multifocal epileptic activity prior to the onset of clinically apparent seizures and there is evidence suggesting that these changes can be reversed by treatment with vigabatrin,32 33 giving better control of epilepsy and improving the cognitive and behavioural outcome 34.…”
Section: Discussionmentioning
confidence: 99%
“…Type and severity of seizures, especially infantile spasms, along with early age of seizure onset also appear to be associated with increased likelihood of cognitive and behavioral difficulties particularly if seizures are not controlled [812]. Similar associations have been reported for higher risk for ASD in TSC [9, 1315], and it has been suggested that epilepsy may be an independent predictor of intellectual ability in TSC [7, 10, 16]. At this time, it is unclear as to whether neurodevelopmental disorders are caused by the underlying brain abnormalities seen in TSC, subsequent development of epilepsy, or both [17].…”
Section: Introductionmentioning
confidence: 88%
“…Features of epilepsy 58 , neuropathology 912 , genetics 13,14 as well as the timing and type of mechanism-based medications 1518 have been reported as risk factors for intellectual disability and/or autism in individuals with TSC. Many of these proposed risk factors are illustrated in these case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberous Sclerosis Complex (TSC) is one of the leading causes of syndromic autism 2,3 , and nearly half of the population is affected by intellectual disability 4 ; however, the predictors and causation are unknown. Features of epilepsy 58 , neuropathology 912 , genetics 13,14 as well as timing and type of mechanism-based medications 1518 have been linked to developmental outcomes. However, none of these studies have reported details about the individuals’ infant presentation making it difficult to fully interpret the results.…”
Section: Introductionmentioning
confidence: 99%